MECHANISMS FOR IMPROVING PUBLIC RELATIONS SERVICES IN THE PUBLIC ADMINISTRATION SYSTEM: INTERNATIONAL AND NATIONAL EXPERIENCE - Mansur Yunusov (International Journal of Literature and Language Studies, 2026)
Abstract. This article presents a comparative analysis of mechanisms for improving public relations services in the public administration system based on international and national experience. It examines modern approaches to the development of government communication, institutional reforms, and models of strategic communication. Special attention is given to improving information policy, ensuring transparency and accountability, and strengthening trust between the state and society.